Development of Mobile Laboratory for Viral Hemorrhagic Fever Detection in Africa. (15th June 2018) - Weidmann, Manfred; Faye, Ousmane; Faye, Oumar; Abd El Wahed, Ahmed; Patel, Pranav; Batejat, Christophe; Manugerra, Jean Claude; Adjami, Aimee; Niedrig, Matthias; Hufert, Frank T; Sall, Amadou A
Abstract : We developed a mobile laboratory for molecular detection of viral hemorrhagic fever viruses for an African team that tested its function during several outbreaks. This was the first team deployed onsite during the Ebola outbreak in West Africa 2014–2016. Abstract: Background: A mobile laboratory transportable on commercial flights was developed to enable local response to viral hemorrhagic fever outbreaks. Methods: The development progressed from use of mobile real-time reverse-transcription polymerase chain reaction to mobile real-time recombinase polymerase amplification. In this study, we describe various stages of the mobile laboratory development. Results: A brief overview of mobile laboratory deployments, which culminated in the first on-site detection of Ebola virus disease (EVD) in March 2014, and their successful use in a campaign to roll back EVD cases in Conakry in the West Africa Ebola virus outbreak are described. Conclusions: The developed mobile laboratory successfully enabled local teams to perform rapid disgnostic testing for viral hemorrhagic fever.